Prevalence and risk of psychiatric disorders as a function of variant rape histories: results from a national survey of women - Zinzow, Heidi M. (2011)
PURPOSE: Rape is an established risk factor for mental health disorders, such as posttraumatic stress disorder (PTSD), major depressive episodes (MDE), and substance use disorders. The majority of studies have not differentiated substance-involved rape or examined comorbid diagnoses among victims. Therefore, the aim of the present study was to estimate the prevalence of common trauma-related psychiatric disorders (and their comorbidity) in a national sample of women, with an emphasis on distinguishing between rape tactics. A secondary objective was to estimate the risk for psychiatric disorders among victims of variant rape tactics, in comparison to non-victims. METHODS: A nationally representative population-based sample of 3,001 non-institutionalized, civilian, English or Spanish speaking women (aged 18–86 years) participated in a structured telephone interview assessing rape history and DSM-IV criteria for PTSD, MDE, alcohol abuse (AA), and drug abuse (DA). Descriptive statistics and multivariate logistic regression analyses were employed. RESULTS: Women with rape histories involving both substance facilitation and forcible tactics reported the highest current prevalence of PTSD (36%), MDE (36%), and AA (20%). Multivariate models demonstrated that this victim group was also at highest risk for psychiatric disorders, after controlling for demographics and childhood and multiple victimization history. Women with substance-facilitated rapes reported higher prevalence of substance abuse in comparison to women with forcible rape histories. Comorbidity between PTSD and other psychiatric disorders was higher among rape victims in comparison to non-rape victims. CONCLUSIONS: Researchers and clinicians should assess substance-facilitated rape tactics and attend to comorbidity among rape victims. Empirically supported treatments are needed to address the complex presentations observed among women with variant rape histories.